Prospective evaluation of delayed central nervous system (CNS) toxicity of hyperfractionated total body irradiation (TBI) - Wenz, Frederik; Steinvorth, Sarah; Lohr, Frank; Frühauf, Stefan; Wildermuth, Susanne; Kampen, Michael van; Wannenmacher, Michael (International journal of radiation oncology, biology, physics, 2000)
Purpose: Prospective evaluation of chronic radiation effects on the healthy adult brain using neuropsychological testing of intelligence, attention, and memory. Methods and Materials: 58 patients (43 ± 10 yr) undergoing hyperfractionated total body irradiation (TBI) (TBI, 14.4 Gy, 12 × 1.2 Gy in 4 days) before bone marrow or peripheral blood stem cell transplantation were prospectively included. Twenty-one recurrence-free long-term survivors were re-examined 6-36 months (median 27 months) after completion of TBI. Neuropsychological testing included assessment of general intelligence, attention, and memory using normative, standardized psychometric tests. Mood status was controlled, as well. Test results are given as IQ scores (population mean 100) or percentiles for attention and memory (population mean 50). Results: The 21 patients showed normal baseline test results of IQ (101 ± 13) and attention (53 ± 28), with memory test scores below average (35 ± 21). Test results of IQ (98 ± 17), attention (58 ± 27), and memory (43 ± 28) showed no signs of clinically measurable radiation damage to higher CNS (central nervous system) functions during the follow-up. The mood status was improved. Conclusion: The investigation of CNS toxicity after hyperfractionated TBI showed no deterioration of test results in adult recurrence-free patients with tumor-free CNS. The median follow-up of 27 months will be extended.
Gesehen am 22.03.2022